Analysis of doping anisotropy in multisectorial boron-doped HPHT diamonds. (September 2020) - Zubkov, Vasily; Solomnikova, Anna; Koliadin, Alexander; Butler, James E.
Graphical abstract: Highlights: A set of multisectorial HPHT diamonds was precisely investigated by admittance spectroscopy from 25 to 450 K. C–V concentration of free charge carriers in one crystal differs by more than 50 times depending on the growth face. For the first time various activation energies for boron were obtained for sectors of a single-crystal diamond plate. Abstract: A set of single-crystal multisectorial diamond plates, cut from boron-doped high-pressure high-temperature (HPHT) grown crystals, was investigated using admittance spectroscopy methods. The results of admittance measurements demonstrate that the density of free charge carriers in one multisectorial crystal may differ by more than 50 times depending on the growth face and it correlates with boron concentration derived from IR absorption studies. For the first time we have obtained different activation energy for boron in sectors within one single crystal. Based on the experimental data, the difference in impurity capture coefficients along the (111) and (001) faces were numerically estimated for the established HPHT growth process.